Pain and loss: process analysis of mourning - Almeida, Edilene Joceli de; Leitune, Clarissa Santos; Pratini Seger, Ângela Cristina Barrios; Terner, Miriam Lerrer; Raenck da Silva, Daila Alena (Revista de Psicologia da IMED, 2015)
This article aims to provide theoretical basis in order to understand the process of mourning and how to contribute to the understanding of subjectivity observed in the pain of love. As a starting point for the development of this text, we seek to understand the formation of the first emotional bonds and the establishment of early attachment patterns developed in the human’s beings lives. These two assumptions are raised for consideration as standards, are responsible for the devices used by each individual to face the mourning process throughout life. The theoretical framework used to discuss this theme authors were enshrined as Bowlby (1990), Nasio (2007) and Worden (1998; 2013).From this study, we believe will be able to offer contributions to psychotherapists who work with this theme, helping them in the management of patients with this condition. This discussion points the need of working with the individual to adapt to a new life, developed without the physical presence of the beloved, establishing an emotional repositioning and find a new sense of life.